Modernizing Court Through Communication Of Ikahi And Information Technology Generalization - Pakpahan, Novritsar Hasintongan (Judex Laguens, 2023)
The establishment of modern judiciary begs the question whether modernity would serve just law properly or simply become another legal challenge for judges within the judiciary. The questions of the research formulated into how does IKAHI keeps the synergy between its member to communicate judges’ difficulties and how does IKAHI supports the idea of generalizing the perception of IT usage for judges in case trials. The role of the study would be beneficial in improving knowledge and application principle in IKAHI action. The result of the data shown positive aspect and proves the main theory and idea. The article is discussed in a deductive method. The main findings of the article is that modernization of court can only be achieved if the use of IT in court has been generalized so that there wouldn’t be contradiction or conflict through the use of electronic judgment templates and use of Google Meet for criminal court trials.